Exploration of Whatsapp Application as Learning Media in Vocational Schools Reviewed from the Teacher's Perspective - Rhepita Hindun Pangesti Sekarkedhaton; Sri Sumarni; Fajar Danur Isnantyo; Rini Anggrainingsih (Universitas Negeri Yogyakarta, 2024)
Background: Whatsapp is widely used as a learning medium to make it easier for teachers to send files of school assignment documents and learning materials to students. This study aims to explore the effectiveness of use, constraints, and solutions in using the Whatsapp application as a learning medium in vocational schools from the teacher's perspective. This research is a qualitative study with a narrative inquiry approach. Methods: The sampling method using purposive sampling obtained a sample size of 6 participants including teachers who have active teaching status and have implemented WhatsApp as a learning medium in their subjects. Interviews were conducted to collect data. Data were analyzed by content analysis using the QSR Nvivo application. Results: 1) the exploration of the use of Whatsapp application as a learning medium in vocational schools in the teacher's perspective was obtained in two categories, including, a) media: discussion, information, evaluation, communication, and b) learning process: offline learning support, and material sharing. (2) obstacles in the use of the Whatsapp application as a learning medium in vocational schools from the teacher's perspective include, a) user aspects: competence in using technology, lack of activity, lack of focus, and b) technical: wifi network, internet quota, and student devices. (3) Solutions in overcoming obstacles in using the Whatsapp application as a learning medium in vocational schools from the teacher's perspective include, a) school facilities: wifi network, whiteboards, and b) improvement efforts: interaction, and competence.Conclusion: The use of WhatsApp applications as a learning media in SMK from the perspective of teachers is said to be effectively used as a medium and support the learning process. The obstacles that teachers often encounter include user constraints and technical obstacles, with the solution taken to improve user competence and optimize the school facilities that have been provided.